5th International Postgraduate Conference on Pharmaceutical Sciences 2017 (iPoPS 2017) - Uitm Selangor, Faculty Of Pharmacy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
WELCOME MESSAGE FROM THE VICE CHANCELLOR OF UNIVERSITI TEKNOLOGI MARA (UiTM) Assalamualaikum wbt I would like to congratulate the Postgraduate Society of Faculty of Pharmacy, UiTM Puncak Alam for organising the 5th International Postgraduate Conference on Pharmaceutical Sciences 2017 (iPoPS 2017). This conference has been successfully organised since 2012 by the postgraduate students together with the Faculty of Pharmaceutical Sciences, Tokyo University of Science, Japan without fail. This symbolises the strong collaboration between UiTM and TUS towards academic excellence, which enhances our academic visibility. UiTM has been ranked top 200 in the QS World University Ranking by subject 2017 for Pharmacy & Pharmacology. This is a big achievement for a young faculty of 14 years. On that note, contributions from the postgraduates play an important role in the development of human capital headed for a personified nation with humanistic values, forward thinking with an edge in entrepreneurship. Postgraduate students nowadays not only face challenges in completing their studies but also competing with the fast pace of ever changing technology. Therefore, we need to allow their full integration into the global knowledge society together with international collaboration to advance the quality of higher education worldwide. Participation in event with different cultures and background like iPoPS 2017 helps develop articulate thinking and inspire healthy competition of ideas among the young, budding research generation in Malaysia. Hopefully, by continuing to invite eminent speakers from all over the world, the Conference will gain its recognition in the international research community and make UiTM soar upwards. We trust this Conference will be a success and carry on for years to come. Congratulations! EMERITUS PROFESSOR DATO' DR. HASSAN SAID Vice-Chancellor Universiti Teknologi MARA (UiTM)